Selected Principles of Pankseppian Affective Neuroscience - Davis, Kenneth L.; Montag, Christian (Frontiers in Neuroscience, 2019)
In the early nineties of the twentieth century Jaak Panksepp coined the term “Affective Neuroscience” (AN) today being accepted as a unique research area in cross-species brain science. By means of i) electrical stimulation, ii) pharmacological challenges, and iii) brain lesions of vertebrate brains (mostly mammalian), Panksepp carved out seven primary emotional systems called SEEKING, CARE, PLAY and LUST on the positive side, whereas FEAR, SADNESS and ANGER belong to the negative affects. Abundant research into human clinical applications has supported the hypothesis that imbalances in these ancient primary emotional systems are strongly linked to psychiatric disorders such as depression. The present paper gives a concise overview of Panksepp's main ideas. It gives an historical overview of the development of Panksepp’s AN thinking. It touches not only areas of neuroscience, but also shows how AN has been applied to other research fields such as personality psychology. Finally, the present work gives a concise overview of the main ideas of AN.